Movement patterns and muscular function before and after onset of sports-related groin pain: A Systematic review with meta-analysis - Kloskowska, P.; Morrissey, D.; Small, C.; Malliaras, P.; Barton, C. (Sports Medicine, 2016)
Sports-related groin pain (SRGP) is a common entity in rotational sports such as football, rugby and hockey, accounting for 12-18 % of injuries each year, with high recurrence rates and often prolonged time away from sport. Objective